2019
DOI: 10.24200/sci.2019.52233.2610
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Extraction of Lactic Acid using Environmentally Benign Green Solvents and Synergistic Mixture of Extractants

Abstract: An environment-friendly reactive extraction method as a novel phase separation technique is considered to extract Lactic Acid (LA) from the aqueous solution by means of environmentally benign green diluents along with a synergistic mixture of extractants. Reactive extraction of LA was carried out through a synergistic mixture of extractants (trioctylamine (TOA), Aliquat336, and tridodecylamine (TDDA)), organic solvents, and non-toxic and biocompatible green diluents. According to the various investigated LA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…The synergism of these extractants (TOMAC+TOA) has been provided the higher LA extraction efficiency than their individual applications during the extraction process [17,37]. This extraction efficiency has been found better than the individual extractants [43,44].…”
Section: Fig3 Effect Of the Phase Ratio And Extractant Ratio On The mentioning
confidence: 97%
“…The synergism of these extractants (TOMAC+TOA) has been provided the higher LA extraction efficiency than their individual applications during the extraction process [17,37]. This extraction efficiency has been found better than the individual extractants [43,44].…”
Section: Fig3 Effect Of the Phase Ratio And Extractant Ratio On The mentioning
confidence: 97%
“…To enhance the extraction yield, the different extractants with solvents can be used in a single organic phase mixture, and this is called synergetic extraction. Positive synergism appears when the hydrophobicity of the extracted complex is improved by solvation, and it is done by the addition of extractants with a high polarity difference. …”
Section: Reactive Extraction: Intensified Approachmentioning
confidence: 99%
“…Researchers have approached different categories of extractants to intensify the reactive extraction process for various organic acids and their salts. The equilibrium and kinetic models are used to investigate the probable reaction regime, rate, and mechanism of the reactive extraction. ,, Investigators have also used the mixture of extractants with solvents in a single unit and discussed their synergistic and antagonistic experimental results on the extraction of the organic acids. The in situ extraction and extractive fermentation studies on organic acid recovery are also approached by some researches. The selective studies on reactive extraction of organic acids with aminic extractants, phosphoric extractants, and hydrophobic ionic liquids are mentioned in Tables , , and , respectively.…”
Section: Reactive Extraction: Intensified Approachmentioning
confidence: 99%
“…Meanwhile, TBP is solvating extractant that contains oxygen bonded to phosphorus. These extractants were proven to benefit the extraction of organic acids in previous study (Kumar and Thakur, 2019;Inyang and Lokhat, 2020).…”
Section: Selection Of Base Extractantmentioning
confidence: 99%
“…Therefore, a combination of various extractants is applied to the LLE systems for obtaining enhanced extraction efficiency (%) owing to the synergistic effect of extractant (Padhan & Sarangi, 2017). Synergism is defined as cooperation between two carrier molecules to improve the extraction effectiveness and collaboration of two extractants/carriers that further facilitates the transportation of solute from the aqueous to organic phase (Kumar & Thakur, 2019;Sulaiman & Othman, 2017). Recently, the applications of a synergistic mixture of extractants during the various extraction studies have been observed.…”
Section: Introductionmentioning
confidence: 99%